Synthesis of Indolizines and Heterocyclic Chalcones Catalyzed by Supported Copper Nanoparticles. Issue 17 (7th March 2013) - Albaladejo, María José; Alonso, Francisco; Yus, Miguel
<x xml:space="preserve">Abstract</x> Solvent decides: Versatile copper nanoparticles (Cu NPs) on activated carbon have been found to catalyze the multicomponent synthesis of indolizines in dichloromethane and the synthesis of heterocyclic chalcones in the absence of solvent, in both cases, from pyridine‐2‐carbaldehyde derivatives, secondary amines, and terminal alkynes (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>